2013
DOI: 10.1161/circheartfailure.113.000481
|View full text |Cite
|
Sign up to set email alerts
|

Low-Sodium DASH Diet Improves Diastolic Function and Ventricular–Arterial Coupling in Hypertensive Heart Failure With Preserved Ejection Fraction

Abstract: Background Heart failure with preserved ejection fraction (HFPEF) involves failure of cardiovascular reserve in multiple domains. In HFPEF animal models, dietary sodium restriction improves ventricular and vascular stiffness and function. We hypothesized that the sodium-restricted Dietary Approaches to Stop Hypertension diet (DASH/SRD) would improve left ventricular diastolic function, arterial elastance, and ventricular-arterial (V-A) coupling in hypertensive HFPEF. Methods and Results Thirteen patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 43 publications
3
118
0
7
Order By: Relevance
“…Although not statistically significant, reductions in LV mass index, relative wall thickness and increased LV ejection fraction, stroke volume, and cardiac output were also reported (Hummel et al. 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Although not statistically significant, reductions in LV mass index, relative wall thickness and increased LV ejection fraction, stroke volume, and cardiac output were also reported (Hummel et al. 2013). …”
Section: Discussionmentioning
confidence: 99%
“…There are studies showing that salt restriction is necessary (5), however, there is also data showing that it has no benefit. It is suggested that a salt-free diet may cause neurohormonal activation in HF.…”
Section: Is Salt Restriction Necessary? If So How Much?mentioning
confidence: 99%
“…The 2 articles published by Levitan et al 7 and Hummel et al, 8 revitalize core consideration of dietary management in HF. Levitan et al 7 explored the relationship of dietary patterns consumed before diagnosis with mortality among women with HF who were participants in the Women's Health Initiative (WHI).…”
Section: Articles See P 1116 and 1165mentioning
confidence: 99%
“…In our search for the silver bullet, we have overlooked the silver plate. Using a different approach, Hummel et al 8 reported findings from a clinical trial conducted among 13 patients with treated hypertension and HF with preserved ejection fraction. Citing evidence in animal models that sodium restriction improves ventricular and vascular stiffness and function, these authors fed a sodium-restricted version (sodium intake of 50 mmol or 1150 mg/2100 kcal) of the DASH diet (DASH/sodium restricted diet [SRD]) with an anticipated outcome of improved left ventricular diastolic function.…”
Section: Circ Heart Failmentioning
confidence: 99%
See 1 more Smart Citation